Enhancing Professional Communicative Competencies through AI: Pedagogical and Psychological Impacts on Students in the Classroom - Iskandarova Sharifa Madaliyevna; Ganieva Dilafruz (Euro Asian Journal Publishing, 2023)
Artificial intelligence (AI) is increasingly penetrating the educational environment, opening new opportunities to improve professional communication competencies among students. Considering this, it is important to investigate the pedagogical and psychological effects of AI on students in the classroom. This study aims to investigate the impact of AI on learning, specifically on the development of students' communication skills. We will examine how AI can help improve these skills and discuss possible problems and challenges. In addition, we will discuss pedagogical strategies and approaches that can help optimize the use of AI in the classroom. Our goal is to provide educators and researchers with valuable insights and recommendations for using AI to improve students' professional communication competencies
Keywords: Artificial Intelligence; education; learning